Usulan Rancangan Ulang untuk Area Makan di Dr. Mochtar Riady Student Center Universitas Ma Chung Malang - Priskila Mega Octiandriani; Teguh Oktiarso; Yuswono Hadi (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2022)
This study aimed to propose a layout design for the dining area of Dr Mochtar Riady Student Center, Universitas Ma Chung using ergonomics to maximize the area and support facilities. Currently, the dining area is not utilized optimally, and the facilities are inadequate. The study utilized an ergonomic approach to develop a layout design that can maximize the area and support facilities on the 1st and 2nd floors. The proposed design includes an increase in tables from 36 to 138, chairs from 190 to 652, electrical contact areas from 3 to 22, and trash bins from 3 to 14. Additionally, the design includes new facilities for stands, booths, sinks, and return racks to enhance the dining experience. The proposed layout design can provide a comfortable and ergonomic dining area for students, employees, and lecturers. The results of the study can be used as a reference for other universities in optimizing their dining areas.